2010
DOI: 10.1086/656369
|View full text |Cite
|
Sign up to set email alerts
|

Biological Determinants of Immune Reconstitution in HIV‐Infected Patients Receiving Antiretroviral Therapy: The Role of Interleukin 7 and Interleukin 7 Receptor α and Microbial Translocation

Abstract: Both the extent of immune depletion prior to ART and IL-7Rα haplotype 2 are important determinants of time to CD4(+) T cell recovery to counts of >500 cells/μL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
102
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 48 publications
19
102
5
Order By: Relevance
“…[25][26][27][28][29][30][31] We recently demonstrated by using a multivariable model that IL-7Ra haplotype-2 was a significant predictor of more rapid CD4 T-cell recovery following suppressive cART in an Australian-based largely Caucasian HIVinfected cohort. 22 Consistent with observations in haplotype-2 carriers in HIV-uninfected cohorts, 9,11,32,33 we found that HIV-infected patients who were homozygous for haplotype-2 had significantly lower concentrations of sIL-7Ra compared with non-haplotype-2 carriers. 22 We therefore proposed that the reduced sIL-7Ra levels in haplotype-2 carriers may increase the availability of IL-7 to bind to membrane-bound IL-7Ra on T-cells, leading to faster CD4 T-cell recovery.…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…[25][26][27][28][29][30][31] We recently demonstrated by using a multivariable model that IL-7Ra haplotype-2 was a significant predictor of more rapid CD4 T-cell recovery following suppressive cART in an Australian-based largely Caucasian HIVinfected cohort. 22 Consistent with observations in haplotype-2 carriers in HIV-uninfected cohorts, 9,11,32,33 we found that HIV-infected patients who were homozygous for haplotype-2 had significantly lower concentrations of sIL-7Ra compared with non-haplotype-2 carriers. 22 We therefore proposed that the reduced sIL-7Ra levels in haplotype-2 carriers may increase the availability of IL-7 to bind to membrane-bound IL-7Ra on T-cells, leading to faster CD4 T-cell recovery.…”
Section: Introductionsupporting
confidence: 90%
“…22 Consistent with observations in haplotype-2 carriers in HIV-uninfected cohorts, 9,11,32,33 we found that HIV-infected patients who were homozygous for haplotype-2 had significantly lower concentrations of sIL-7Ra compared with non-haplotype-2 carriers. 22 We therefore proposed that the reduced sIL-7Ra levels in haplotype-2 carriers may increase the availability of IL-7 to bind to membrane-bound IL-7Ra on T-cells, leading to faster CD4 T-cell recovery.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations